The Relationship Of Maternity Companion Support To The Anxiety Of Maternity Mothers Facing The Primigravida Delivery Process At The Barusjahe Health Center, Karo Regency - Br Tarigan, Suasana; Ridesman, Ridesman; Pasaribu, Riska Susanti (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Childbirth is a normal physiological occurrence in life. Anxiety is an unpleasant emotional state characterized by fear as well as stressful physical symptoms. The impact of anxiety that is not treated seriously will affect the physical and psychological both mother and fetus. Mothers who experience stress and anxiety will experience an increase in the release of stress hormones, causing disruption of blood flow in the uterus and resulting in weak uterine muscle contractions. This event causes a longer labor process (long partus) and the risk of sectio caesaria as much as 54.8%. While the risk to the baby can cause premature birth, giving birth to babies with low birth weight (BBLR), emergency (fetal distress) and in the long term related to behavioral and emotional disorders of the child. The type of research is quantitative analytic with a cross sectional approach. The research was conducted in the working area of the Barus Jahe Health Center, Karo Regency, carried out in March-June 2023. The study population was all maternity mothers in the working area of the Barus Jahe Health Center totaling 45 people. The sampling technique used is Consecutive Sampling. The data analysis used was univariate analysis and bivariate analysis, the analysis used was Chi Square statistical test (X2) with α = 0.05. The results showed that there were 16 (35.5%) respondents who experienced normal levels of anxiety, 8 (17.8%), respondents experienced mild levels of anxiety, 7 (15.5%) respondents experienced moderate levels of anxiety and 14 (31.1%) respondents experienced severe levels of anxiety. The results of the Chi Square test with continuity correction obtained a P value of 0.001 (<0.05), meaning that there is a relationship between childbirth companion support for the anxiety of maternity mothers facing the primigravida delivery process at the Barus Jahe Health Center, Karo Regency. The results of statistical tests can be concluded that there is an effect of childbirth companion support on the anxiety of maternity mothers facing the primigravida labor process at the Barus Jahe Health Center, Karo Regency with a Chi Square value by looking at continuity correction, obtained a P value of 0.001 (<0.05). It is expected that health workers provide education and communication to increase the understanding of childbirth companions in providing psychological support during childbirth.